(untitled) (Journal of Veterinary Medicine and Animal Production, 2021)
The objective of this study was to evaluate fat content and fatty acid (FA) composition of goat meat and adipose tissues at retail outlets in Khartoum State. A total of 25 carcasses of goat were involved in this study. Samples from longissimus dorsi muscle (LD), kidney fat (KF), and subcutaneous fat (SF) were obtained from each carcass for fat extraction and FA analysis. The fat contents were 78.21, 73.76 and 3.6% for KF, SF and LD, respectively. The most abundant FA were oleic, palmitic, and stearic. Oleic was higher (P<0.05) in LD (30.04%) than in SF (25.29%) and KF (17.86%). The stearic was greater (P<0.05) in KF (28.04%) compared to SF (27.29%) and LD (25.37%). Palmitic was higher (P<0.05) in KF (29.54%) than in SF (25.32) and LD (20.8%). The linoleic acid and α-linolenic acids were higher (P<0.05) in LD to compared SF and KF. The total desirable FA, which comprise of stearic acid plus total unsaturated FA were greater (P<0.05) in LD (72.05%), followed by SF (60.86%), and the least proportion (50.7%) was found in KF